Implementation and Derivation Kinematics Modeling Analysis of WidowX 250 6Degreef of Freedom Robotic Arm - Hasan Obied; Manaf K. H. Al-Taleb; Hind Z. Khaleel; Ali F. AbdulKareem (Journal of Engineering and Sustainable Development, 2025)
Many industries use robotic arms to perform tasks like picking and placing. The main goal of this paper is to derive and implement the forward and inverse kinematics of a 6-degree-of-freedom articulated robotic arm. In addition, a closed-form solution is required to design the inverse kinematics, unlike the forward kinematics. Then, the inverse kinematics and forward kinematics modeling were successfully performed on the WidowX 250 6-degree-of-freedom robotic arm. The MATLAB modeling results are compared to the ROS results, which showed a matching percentage of 99%. In addition, the inverse kinematics results revealed a range of solutions that are approximately identified to the desired results, while others were not, such as the value of the third joint angle is obtained at ±1.57 radians. Finally, due to the accuracy value of this comparative work between real ROS and MATLAB derived equations of the WidowX 250 6DOF robot arm, it is concluded that the joints and coordinates of this robot are identified.